Analisis Framing Bahasa Berita Tindak Kriminal pada Media Massa - Syafyahya, Leni; Yades, Efri (Puitika, 2020)
The problem in research, namely how is the choice of words in mass media framing of crime news? What are the techniques and models of mass media framing of crime news? What is the response of the community to the use of non-criminal news language and its influence on society? This study aims to describe and inventory the concept of the crime language news framing in the mass media. The concept of framing described is related to the choice of words in mass media framing, techniques and models of mass media framing of crime news and public response to the use of non-criminal news language and its influence on society. The method used in this study consists of three stages, namely the stage of data collection, the stage of data classification, and the stage of data analysis. Data obtained from print media mass media. Technically, this research was conducted using the method of listening and proficient methods in providing data. The proficient method can be compared with the interview method. In data analysis, editing, coding, and matching methods are used. Based on data analysis, the choice of words in the language of news framing of crimes is generally in favor of the victim. News writers choose words that can accompany the reader's mind to sympathize with the victim. In addition, the focus of the news is framing with cognitive, empathy, and packing techniques. The framing model in crime news language has four structural dimensions of news text as a framing device, namely syntax, script, thematic, and rhetorical. Keyword: framing, language, crime news, and mass media